2013
DOI: 10.7731/kifse.2013.27.5.75
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Relationship of the Left Ventricle in the Supine Position and the Left Lateral Tilt Position (Implication for Cardiopulmonary Resuscitation in Pregnant Patients)

Abstract: Application of the left lateral tilt position has been recommended during cardiopulmonary resuscitation (CPR) of pregnant patients. However, the left lateral tilt could displace the left ventricle (LV) besides the gravid uterus and may compromise the cardiac pump mechanism of CPR. Thus, we investigated the effect of left lateral tilt on the spatial relationship between the anterior-posterior axis (AP axis), which represents the direction of sternal displacement during CPR, and the LV. We retrospectively review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A study on mannequin demonstrated that a tilt of 27° was enough during chest compression to stop mannequin from falling but with the limitation of achieving 80% of force for CCs as compared to supine position [121]. A virtual gastroscopy demonstrated lateral displacement of the heart on lateral tilt offsetting the pumping action of chest compression [122]. A study utilized MRI to demonstrate compression of inferior vena cava and partial release on the lateral tilt of 30° in pregnant patients as compared to non-pregnant patients [123].…”
Section: Cardiac Arrest In Pregnancymentioning
confidence: 99%
“…A study on mannequin demonstrated that a tilt of 27° was enough during chest compression to stop mannequin from falling but with the limitation of achieving 80% of force for CCs as compared to supine position [121]. A virtual gastroscopy demonstrated lateral displacement of the heart on lateral tilt offsetting the pumping action of chest compression [122]. A study utilized MRI to demonstrate compression of inferior vena cava and partial release on the lateral tilt of 30° in pregnant patients as compared to non-pregnant patients [123].…”
Section: Cardiac Arrest In Pregnancymentioning
confidence: 99%